Hubungan Character Strength dengan Subjective Well-Being pada Mahasiswa Kota Bandung yang Melaksanakan E-learning - Shafira Azzahra Wiradikara; Susandari (Bandung Conference Series: Psychology Science, 2022)
Abstract. The COVID-19 pandemic has caused several impacts on all aspects of society, one of which is in the field of education. In an effort to prevent the spread of the virus, the Government of Indonesia through the Ministry of Education and Culture prohibits face-to-face learning activities and switches to e-learning. This unexpected transition has the potential to cause learning to be not optimal and not ideal and can have an impact on student conditions, one of which is the student's Subjective Well-Being condition. This study aims to see the correlation between the overall characters in Character Strength and Subjective Well-Being of college students in the city of Bandung who carry out learning using e-learning. The participants in this study were 270 college students in the city of Bandung who were obtained using cluster sampling techniques. The research instruments are Values ​​in Action Inventory of Strengths (VIA-IS), Statistics With Life Scale (SWLS), and Positive and Negative Affect Scale (PANAS). The analysis used is Pearson correlation. The results of this study indicate that there is a positive relationship between Character Strength and Subjective Well-Being in Bandung City college students who implement e-learning. That is, the more characters in Character Strength increase, the Subjective Well-Being will also increase. The character that is strongly correlated with Subjective Well-Being is Vitality (r=0.637). Abstrak. Pandemi COVID-19 menyebabkan beberapa dampak pada seluruh aspek masyarakat, salah satunya terdapat pada bidang pendidikan. Sebagai upaya untuk mencegah penyebaran virus tersebut maka Pemerintah Indonesia melalui Kemendikbud melarang kegiatan pembelajaran tatap muka dan beralih pada pembelajaran e-learning. Peralihan yang tidak diduga ini berpotensi mengakibatkan pembelajaran menjadi tidak optimal serta tidak ideal dan dapat memberikan dampak pada kondisi mahasiswa, salah satunya adalah keadaan Subjective Well-Being mahasiswa. Penelitian ini bertujuan untuk melihat korelasi antara keseluruhan karakter yang ada pada Character Strength dengan Subjective Well-Being mahasiswa di kota Bandung yang melaksanakan pembelajaran menggunakan e-learning. Partisipan dalam penelitian ini adalah 270 mahasiswa perguruan tinggi di kota Bandung yang diperoleh menggunakan teknik cluster sampling. Instrument penelitian ini adalah Values in Action Inventory of Strengths (VIA-IS), Statisfication With Life Scale (SWLS) dan Positive and Negative Affect Scale (PANAS). Analisis yang digunakan adalah korelasi Pearson. Hasil penelitian ini menunjukkan bahwa terdapat hubungan positif antara Character Strength dengan Subjective Well-Being pada mahasiswa Kota Bandung yang melaksanakan e-learning. Artinya, semakin meningkatnya karakter yang ada pada Character Strength maka akan meningkat pula Subjective Well-Beingnya. Karakter yang berkolerasi kuat dengan Subjective Well-Being adalah Vitalitas (r=0,637).